2004
DOI: 10.1007/s00125-004-1337-3
|View full text |Cite
|
Sign up to set email alerts
|

In human gestational diabetes mellitus congenital malformations are related to pre-pregnancy body mass index and to severity of diabetes

Abstract: Aims/hypothesis. This study analysed the relationship between congenital malformations (CM) and severity of gestational diabetes mellitus. Methods. A cohort of 2060 infants of mothers with gestational diabetes was studied. Universal screening and 3 rd Workshop-Conference criteria were used to diagnose gestational diabetes. The severity of diabetes was assessed on the basis of previous hyperglycaemia, blood glucose values in diagnostic OGTT, area under the glucose curve, gestational age and HbA 1 c at diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
18

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 37 publications
(47 reference statements)
1
51
1
18
Order By: Relevance
“…We found that GDM did not alter the risk of nervous system malformations. The incidence of these malformations was much lower than the incidence of cardiac malformations, as previously reported by other authors [22,25]. One hypothesis is that early hyperglycaemic exposure of the embryo has different teratogenic effects on cardiac and nervous system tissues.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…We found that GDM did not alter the risk of nervous system malformations. The incidence of these malformations was much lower than the incidence of cardiac malformations, as previously reported by other authors [22,25]. One hypothesis is that early hyperglycaemic exposure of the embryo has different teratogenic effects on cardiac and nervous system tissues.…”
Section: Discussionmentioning
confidence: 44%
“…The excess risk of cardiac malformations observed in this group persisted after the exclusion of women with undiagnosed pregestational diabetes, indicating that mechanisms other than periconceptional maternal blood glucose levels may increase the risk of cardiac malformations [21]. In addition to the severity of diabetes, pre-pregnancy BMI in mothers with GDM was previously shown to be a predictor of congenital malformations in infants [22]. Other teams have shown that high maternal BMI is associated with an increased risk of malformations that is independent of maternal blood glucose levels [23,24].…”
Section: Discussionmentioning
confidence: 70%
“…Indeed, congenital defects are still more frequent in infants of diabetic mothers than in the general population, in spite of adequate hyperglycaemia control in a large proportion of diabetic pregnant women. Recent reports have observed that the correlation between congenital malformations in infants of diabetic mothers and pre-pregnancy BMI is higher than that between congenital malformations and maternal blood glucose values [92], and that oxidative stress makes an important contribution to the increase in neural tube defects [93]. In addition, obesity and hyperinsulinaemia have been suggested as risk factors for neural tube defects in the general population [94].…”
Section: Relevance and Challenges Aheadmentioning
confidence: 99%
“…Oddy et al [55] referred to normal weight as a BMI of between 20 to < 25, which is not according to WHO recommendation and reported the outcome of orofacial cleft in general. In one of the articles, weight was classified according to tertiles and also they did not report the outcome of cleft but only reported congenital malformations [56]. Villamor et al [57], classified weight according to change in weight and so it was excluded.…”
Section: Search Resultsmentioning
confidence: 99%
“…Studies in which orofacial cleft was grouped as a single entity and not subdivided were excluded because it is known that both CP and CLP have different aetiology. Diabetes is considered a confounding variable when examining the association between obesity and orofacial cleft [56]. All studies included in this review did report…”
Section: Discussionmentioning
confidence: 99%